Cloud Computing Deployment and Management: A Collection of Exercises and Tasks with Solutions - Zamuda, Aleš (University of Maribor Press, 2020)
The subject Cloud Computing Deployment and Management is included in the second-cycle Bologna Study Programme Computer Science and Information Technologies as a full-time study unit. This document presents study material for computer exercises in this subject. After an introduction, then individual tasks with solutions to the computer exercises in the subsequent chapters are provided. This is followed by a list of archived files containing the computer format of the provided solutions.